Assessing the use of a mechanical rump pusher in a commercial cattle slaughter plant - Eleanor Wigham; Megan French (Animal Welfare)
Commercial cattle slaughter operations have shown an increasing trend towards automation, with the aim being to improve animal welfare, product quality and efficiency. Several cattle slaughter plants have introduced mechanical rump pushers (RP) prior to the entrance of the stun box to reduce human-animal interaction and facilitate a smoother transition from the raceway to stun box. Presently, there are no data regarding the use of RPs in commercial slaughter environments operating at 40 cattle per hour. Therefore, this study observed normal operations at a UK slaughter plant, which has an RP installed, and assessed the level of coercion required to enter the RP, the use of the RP, cattle behaviour inside the RP and carcase bruising. The RP was used on 267 of the 815 cattle observed (32.8%) and was more likely to be used on dairy cattle and those who received a higher coercion score when entering the RP. Overall, 60 cattle (7.4%) required the highest coercion score and four (0.49%) required the use of the electric goad. Inside the RP, eleven animals slipped (1.8%) and ten vocalised (1.6%) although no incidences were directly associated with RP use. However, increased time restrained in the RP was significantly associated with more gate slams into the RP entrance gate. The use of the RP was not significantly associated with carcase bruising. These results are encouraging, and although it cannot be concluded that the presence of an RP improves cattle welfare at slaughter, use of automation within cattle slaughter facilities warrants further investigation.